Pre and postoperative diarrhoea associated with neuroblastoma resection - A systematic review of published studies - Alikärri Suvi; Raitio Arimatias; Losty Paul D (Netherlands, 2025)
Neuroblastoma is a malignant tumour affecting 10.5/1 million children annually. It arises from sympathetic nervous system precursor cells and is most frequently found in the adrenal gland and abdominal paravertebral ganglia. Diarrhoea as a presenting symptom of neuroblastoma is uncommon and usually linked to vasoactive intestinal peptide (VIP) tumour secretion. Even more rarely, postoperative diarrhoea may follow neuroblastoma tumour resection. Published studies generally associate postoperative diarrhoea with subadventitial tumour resection. These findings are however based on a handful of reports. This systematic review therefore aims to analyse the true incidence of postoperative diarrhoea and its morbid correlation with the extent/type of surgical resection. Pubmed/Embase databases were searched according to PRISMA guidelines. Final analysis consisted of 16 studies: N = 779 patients. Postoperative diarrhoea was significantly more common in all patients who underwent subadventitial resection compared to non subadventitial resection, p < 0.001 (OR 25.9, 95% CI 9.3-72.4). 5-year survival rates were equivalent in both groups. Preoperative diarrhoea was rarely reported in studies and always strongly linked to elevated VIP secretion. In the majority of neuroblastoma patients, preoperative diarrhoea ameliorated after gross tumour resection with elevated VIP normalized. The operative technique of subadventitial neuroblastoma resection portends significant risk(s) of post operative diarrhoea not seen in those patients undergoing other classical methods of tumour resection with 5-year survival rates strikingly similar. These findings affirm that subadventitial tumour resection should be avoided when undertaking surgery for neuroblastoma to minimize the risk(s) of persistent postoperative diarrhoea.